Small and Medium Enterprises Development and Government Support in Kyrgyzstan - Guo, Shaozheng; N.M., Musaeva; Yuan, Haohe; Yang, Ping; Baktygul , Esenalieva; Pan, Depeng (International Journal of Accounting and Economics Studies, 2025)
Small and medium enterprises (SMEs) play a pivotal role in the economic development of ‎transitioning economies, including Kyrgyzstan. This study examines the interplay between ‎SME development and government support in Kyrgyzstan, focusing on policy frameworks, ‎financial incentives, and institutional mechanisms. Drawing on qualitative and quantitative ‎data, the analysis highlights the challenges SMEs face, including limited access to finance, ‎regulatory barriers, and inadequate infrastructure. The paper evaluates the effectiveness of ‎government initiatives, such as tax incentives and subsidized loans, in fostering SME growth. ‎Findings suggest that while government support has facilitated some progress, structural ‎inefficiencies and policy implementation gaps hinder sustainable development. ‎Recommendations include enhancing public-private partnerships and streamlining regulatory ‎processes to bolster the SME ecosystem. This study contributes to the literature on economic ‎development in post-Soviet states and provides actionable insights for policymakers‎.
Keywords: Small and Medium Enterprises; Government Support; Economic Development; ‎Kyrgyzstan; Policy Implementation